Relationship Between Political Risk, Corruption and Infrastructure and Foreign Direct Investment Inflows to Yemen - Alrezaki, Mohammed Abdulkarem Mohammed (2009)
Foreign Direct Investment (FDI) plays an important role in the growth and development of emerging economies. And it has been considered a powerful mechanism to achieve rapid economic growth in the developing countries. However Arab countries have been performing poorly in attracting FDI inflows relative to other developing countries since the early 1990s. This study examines the impacts of special host country factors namely political risk, corruption, and infrastructure on the inflow of foreign direct investment (FDI) into Yemen between 2003 and 2007. Results indicate that high levels of political risk and corruption lead to low levels of FDI inflows into Yemen. With political risk being significantly and negatively correlated to the FDI inflows. The findings also show that infrastructure variable with three proxies (road length, operating telephone line, and electric power generation capacity) are insignificantly and positively correlated with FDI.